Factors Affecting Adolescent Behavior Toward Consumption of Blood Addition Tablets in Adolescent Girls at SMA Negeri 1 Abung Tinggi North Lampung Year 2024 - Syehasinah, Indah; Kumalasari, Desi (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: The purpose of this study was to analyze the factors that influence the behavior of taking blood supplement tablets in adolescent girls at SMA Negeri Abung Tinggi North Lampung. Method: This type of research is a type of quantitative research with the approach method used cross sectional. Populas, as many as 182 adolescent girls. sample as many as 101 respondents, sample technique using random sampling. The research was conducted on December 02, 2024 at SMA Negeri Abung Tinggi North Lampung. The instrument used was a questionnaire. Data analysis using the Chi-square test. Result: The results of the study obtained 3 factors associated with the behavior of taking blood add tablets in adolescent girls at SMA Negeri Abung Tinggi Lampung Utara, namely the knowledge factor, the family support factor, the attitude with the obtained ρ (sig) value <0.05 while the teacher and peer support factor obtained ρ (sig) value> 0.05 means that there is no relationship with the behavior of taking blood add tablets in adolescent girls at SMA Negeri Abung Tinggi Lampung Utara. Conclusion: The Chi-square statistical test showed a significant relationship between knowledge, attitude, and family support with the behavior of taking blood supplement tablets. However, there was no significant relationship between teacher and peer support with the behavior.